2011
DOI: 10.1186/1471-2164-12-448
|View full text |Cite
|
Sign up to set email alerts
|

A global view of porcine transcriptome in three tissues from a full-sib pair with extreme phenotypes in growth and fat deposition by paired-end RNA sequencing

Abstract: BackgroundElucidation of the pig transcriptome is essential for interpreting functional elements of the genome and understanding the genetic architecture of complex traits such as fat deposition, metabolism and growth.ResultsHere we used massive parallel high-throughput RNA sequencing to generate a high-resolution map of the porcine mRNA and miRNA transcriptome in liver, longissimus dorsi and abdominal fat from two full-sib F2 hybrid pigs with segregated phenotypes on growth, blood physiological and biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
82
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 57 publications
12
82
8
Order By: Relevance
“…In similar studies of pigs (Chen et al, 2011;Esteve-Codina et al, 2011) and cattle (Huang et al, 2012), in which 61.6-77.8% of reads were matched to the reference genome, our results were comparable for sheep. The percentage of reads mapped to the reference genes were lower than that mapped to the O. aries genome, a result potentially due to the GC content, type of cells, and other reasons (McIntyre et al, 2011;Sendler et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In similar studies of pigs (Chen et al, 2011;Esteve-Codina et al, 2011) and cattle (Huang et al, 2012), in which 61.6-77.8% of reads were matched to the reference genome, our results were comparable for sheep. The percentage of reads mapped to the reference genes were lower than that mapped to the O. aries genome, a result potentially due to the GC content, type of cells, and other reasons (McIntyre et al, 2011;Sendler et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
“…The most common AS identified in our research was IR, in both Mongolian and Lanzhou fat-tailed sheep. Our results were similar to those for rice (Zhang et al, 2010), but different from those for pigs (Chen et al, 2011) and Dorper and small-tailed Han sheep (Zhang et al, 2013), in which A3SS was identified as the most common AS. Our results also differed from those of humans (Sultan et al, 2008), in which ES was the primary type of AS.…”
Section: Discussionsupporting
confidence: 58%
“…1B). Compared with the reports for non-model organisms of sheep [13], pigs [4] and bovine [31], in which 61.4e75.0% of reads mapped to the reference genome, our mapping percentage was pretty comparable and even better, which are ensuring reliable downstream analysis.…”
Section: Summary Of the Raw Sequence Readsmentioning
confidence: 56%
“…It has been demonstrated that miRNAs are stable and resistant to extreme pH and temperature in body fluids (29,30), and serum miRNAs have been reported as the best biomarker for cancer diagnosis (31,32). Thus, the use of serum as a diagnostic tool for patients with RCC is of relevance.…”
Section: Discussionmentioning
confidence: 99%